EFEKTIVITAS METODE MONTESSORI BERBANTU MOVABLE ALPHABET TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 SD DAPUAN SWASTA SURABAYA - Mas Wardah Mufidah; Muhammad Assegaf Baalwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of the Montessori method assisted by Movable Alphabet in improving the early reading skills of grade 1 students of SD Dapuan Swasta Surabaya. The study used a pre-experimental One-Group Pretest-Posttest design with a sample of 20 students. The Montessori method was applied through direct activities using Movable Alphabet as an interactive visual aid to recognize letters and combine words. Data were collected through pretest and posttest tests, then analyzed using the Shapiro-Wilk normality test. The results of the normality test showed that the data were not normally distributed with a significance value of pretest (0.000) and posttest (0.000) less than 0.05, then continued with the Wilcoxon signed rank test hypothesis test obtained a significance value of 0.000 <0.05. The conclusion of the study proves that the Montessori method assisted by Movable Alphabet is effective in improving early reading skills, marked by an increase in the average score of 77.75 points. Based on the results of the study, it can be said that the Montessori method using movable alphabet is effective for students' initial reading abilities.